NATIONAL PROTECTION OF THE INTELLECTUAL RIGHTS OF BROADCASTING ORGANIZATIONS - Mohammad Musallam Alzawahreh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to determine the national protection for works prepared by broadcasting organizations, and the importance of this study is shown by determining the scope of national protection for works prepared by broadcasting organizations, and the means of their procedural, civil and criminal protection, the researcher applied the descriptive, analytical and comparative approaches to study the legal texts surrounding the nature of the subject. The Jordanian legislator has dealt with all the cases in which the work may appear to determine the term of protection. The Jordanian legislator also granted broadcasting organization programs a protection period of twenty years, and the free legislator excluded works from the scope of application of protection and considered them as acts that do not constitute an attack on the work. The research came out with several recommendations which are mentioned at the end.